Thank You for Dying for Our Country : Commemorative Texts and Performances in Jerusalem - Noy, Chaim, 1968- (Oxford studies in the anthropology of language., 2015)
Combining ethnographic, semiotic, and performative approaches, the book examines texts and accompanying acts of writing in a visitor book in a national historic site. The visitor book is viewed as a mobilised stage, a communication medium, where visitors' public performances are presented, and where acts of collective participation are authored and composed. The study contextualises the visitor book within its material and ideological environment.